Cultural Activities of Jagatpal Mahavihar and its Impact on Devotees of Kirtipur - Bajracharya, Bajramuni (Mangal Research Journal, 2021)
Jagatpal Mahavihar is a traditional Buddhist monastery of Kirtipur, situated at ChilancvoVihar, Kirtipur Municipality, Ward 10. There stands a complex area covered by five main Caityas in the central part of the monastery. The main aim of this study is to explore the cultural activities of the monastery, to assess the previous trend of renovation culture, and to find out the devotees the past renovation about the Caitya. There live 160 male members Vajracharyas among whom I selected fifteen as Ajus in the monastery as data for my study. I have applied the ethnographic method and entertained observation, and open interviews with the concerned members of the Guthi during the course of data collection. Photographies, inscriptions, books, and artifacts have been used for description. I started my research during Nepal earthquake 2015 and completed it in two years. My study revealed the series of events as the renovation acts. During renovation of the Caitya, the Ajus completed the amnesty worship; pulled the pinnacle by using a cow; removed nyasa and kept it in a secret place; installed the soul of the god by Pranpratistha pooja; and during the renovation of the center, devotees kept religious valuable things for merit. While building and renovating the Caitya in past it was revealed that ancestors used crystal, Fudan, images of Buddha, copper plate, gold, and silver and other valuable ornaments. Some archaeological artifacts have also proved that the last renovation had been done during the period of late King Tribhuvan Bir Bikram Shah Dev.